Photocarrier thermalization bottleneck in graphene - Yadav, Dinesh; Trushin, Maxim; Pauly, Fabian (My University, 2019)
We present a theoretical study of photocarrier dynamics in graphene due to electron-phonon (EP) interactions. Using the relaxation-time approximation (RTA) with parameters determined from density functional theory (DFT) and a complementary explicitly solvable model, we show that the photocarrier thermalization time changes by orders of magnitude, when the excitation energy is reduced from 1 eV to the 100 meV range. In detail the ultrafast thermalization at low temperatures takes place on a femtosecond timescale via optical phonon emission, but slows down to picoseconds once excitation energies become comparable with these optical phonon energy quanta. In the latter regime thermalization times exhibit a pronounced dependence on temperature. Our DFT-based model includes all the inter- and intraband transitions due to EP scattering. Thanks to the high melting point of graphene we extend our studies up to 2000 K and show that such high temperatures reduce the photocarrier thermalization time through phonon absorption.
Keywords: 530